Black students' experiences of transformation at a previously "white only" South African university: a photovoice study. Issue 11 (2nd September 2017) - Cornell, Josephine; Kessi, Shose
ABSTRACT: South African higher education has faced much structural transformation since the dismantling of apartheid, and yet remains a racialized space. Despite a stated commitment to transformation in university policy nationally, lay discourses of transformation are highly contested. In these debates, black students are often represented in stigmatizing ways; which affect students' self-esteem and academic performance. This paper explores black students' experiences of transformation at the University of Cape Town (UCT), a previously "white only" university, based on the results of a photovoice project. The data analysed are drawn from focus groups, personal reflections, photographs and written stories exploring their experiences at UCT. The findings suggest that there is a failure of transformation at UCT, characterized by the dominance of whiteness in the institution. The paper also discusses how many students internalize the negative stereotypes they encounter whilst others use coping mechanisms and strategies to resist the discourse of black inferiority.